Sistemas de informações geográficas: elementos para o desenvolvimento de bibliotecas digitais geográficas distribuídas - Silva, Marcel Santos [UNESP] (2006)
The development of technologies of information and communication applied to the Geographical information grow in a considerable way and become more visible the increase of Geographic Information Systems, mainly in governments environments, that worry in supplying the geographic information for more and more people. The target of this work is to present an architecture with elements for the construction of a distributed geographical digital library, using patterns and concepts of the Information Science together with geoprocessing. The concepts of digital libraries and the patterns of metadata for geographical information will be presented, besides the geo-ontologies that contribute to better organization and recovery of geographical information. It was used the Geographic Information Systems and the theory of Information Science, focused mainly to the development of distributed geographical digital library.The proposal for construction of the distributed geographical digital library is on the principle of cooperation among systems and it considers the free access to geographical information, the interoperability facilitated by the standardization of the metadatas and geo-ontologies. The architecture proposed for the development of distributed geographical digital libraries assists the requirements of representations of the information, ways of communications and collection protocols for metadatas and digital objects, facilitating thus, the share of collections of geographical informations distributed at several Geographical Digital Libraries. The links between the geoprocessing and Information Science is pointed out with regard to the structuring of geographical information environment that can be accessed through computers network.